Synthesis and controlled release of cloprop herbicides from cloprop-layered double hydroxide and cloprop-zinc-layered hydroxide nanocomposites - Hashim, Norhayati; Hussein, Mohd. Zobir; Md Isa, Illyas; Kamari, Azlan; Mohamed, Azmi; Mohamad Jaafar, Adila; Taha, Hafsah (Scientific Research Publishing, 2014)
Two phenoxyherbicide nanocomposites, namely cloprop-layered double hydroxide and cloprop-zinc- layered hydroxide nanocomposites, have been synthesized by using co-precipitation and direct reaction method. PXRD pattern showed an expansion of interlayer spacing with the value of 21.0 Å and 22.7 Å for cloprop-layered double hydroxide and cloprop-zinc-layered hydroxide nanocomposite, respectively. It is evident from FTIR and elemental analyses that both nanocomposites were successfully intercalated between the interlayers of layered metal hydroxide. Controlled release of cloprop anion from interlayer of nanocomposites for both cloprop-layered double hydroxide and cloprop-zinc-layered hydroxide nanocomposite into phosphate solution was rapid initially and slow thereafter. The percentage of accumulated release of cloprop anion from cloprop-zinc-layered hydroxide nanocomposite was slightly higher than that from cloprop-layered double hydroxide nanocomposite. Kinetic behavior of cloprop release was governed by pseudo-second-order for cloprop-layered double hydroxide nanocomposite while parabolic diffusion for cloprop-zinc-layered hydroxide nanocomposite. Results from this study highlight the potential of both nanocomposites as capsulated material for controlled release of cloprop phenoxyherbicides anion.